Definition of an adapted cut-off for determining low lean tissue mass in older women with obesity: a comparison to current cut-offs - Maïmoun, Laurent; Serrand, Chris; Mura, Thibault; Renard, Eric; Nocca, David; Lefebvre, Patrick; Boudousq, Vincent; Avignon, Antoine; Mariano-Goulart, Denis; Sultan, Ariane (Scientific reports, 2022)
The prevalence of sarcopenia in patients with obesity varies according to the definition used. The purpose of our study was to: (i) determine the prevalence of sarcopenia in terms of lean tissue mass in older women with obesity using the current cut-offs, (ii) redefine a specific cut-off for low lean tissue mass (LLTM), and (iii) re-determine the prevalence of LLTM using this new cut-off. Appendicular lean mass (ALM) and the ALM index [ALM/height 2 : ALMI(h 2 )] and ALMI/body mass index [ALMI(BMI)] were determined in 791 women with or without obesity. LLMM prevalence was calculated using the current cut-offs: EWGSOP2: ALM < 15 kg and ALMI(h 2 ) < 5.5 kg/m 2 ; FNIH: ALM < 15.02 kg and ALMI(BMI) < 0.51; and IWGS: ALMI(h 2 ) < 5.67 kg/m 2 and cut-offs newly determined from data provided from young women with obesity. ALM, ALMI(h 2 ) and ALMI(BMI) were lower in older compared to young obese women. Using the current cut-offs, a wide distribution of LLTM prevalence (0 to 29.2%) was observed. When the newly determined cut-offs were applied – i.e., ALM < 18.51 kg; ALMI(h 2 ) < 7.15 kg/m 2 , ALMI(BMI) < 0.483, and T-score: [(ALMI(h 2 ) measured)-(2.08 + 0.183*BMI)]/0.72] − the LLTM mass prevalence was 17.37%; 8.47, 14.8 and 12.71%. respectively. This study showed that the current cut-offs for LLTM as criteria for sarcopenia diagnosis are not adapted to the obese population. Although the new “static” cut-offs appeared to be more adapted, a “dynamic” cut-off for ALMI(h 2 ) that took into account the BMI and thus the obesity severity appeared even more relevant.